Studi Korelasional antara Playing Victim dan Keterampilan Berpikir Kritis pada Materi Ikatan Kimia: Correlational Study between Playing Victim and Critical Thinking Skills on Chemical Bonding Materials - Ahmar, Dewi Satria; Azzajjad, Muhammad Fath (Journal of Chemistry Sciences and Education, 2025)
This study aims to determine the relationship between playing victim potential and students' critical thinking skills on chemical bonding material. This study uses a correlational quantitative method with a survey design. The sample consisted of 32 Biology Education students class of 2023 who programmed the Basic Chemistry 1 course, randomly selected. Data were collected through a questionnaire to identify perpetrators and victims of playing victim, as well as essay questions to measure critical thinking skills. The results showed that 27 students were potential perpetrators of playing victim and 5 students as victims. Pearson correlation analysis showed a significant negative relationship between potential playing victim and critical thinking ability (r = -0.681, p < 0.01). This finding reflects the importance of character education and mental strengthening of students to prevent deviant thinking patterns that hinder cognitive development. In the future, the integration of affective education in chemistry learning becomes increasingly relevant.